Fungus-mediated biosynthesis of silica and titania particles - Bansal, Vipul; Rautaray, D.; Bharde, Atul A.; Ahire, Kedar C.; Sanyal, A.; Ahmad, Absar; Sastry, Murali (Journal of Materials Chemistry, 2005)
The synthesis of inorganic materials by biological systems is characterized by processes that occur at close to ambient temperatures, pressures and neutral pH. This is exemplified by biosilicification in marine organisms such as diatoms while laboratory-based synthesis of silica involves extreme temperature and pH conditions. We show here that silica and titania particles may be produced by challenging the fungus Fusarium oxysporum with aqueous anionic complexes SiF62- and TiF62- respectively. Extra-cellular protein-mediated hydrolysis of the anionic complexes results in the facile room temperature synthesis of crystalline titania particles while calcination at 300 degrees C is required for crystallization of silica.

Fungus-mediated biotransformation of amorphous silica in rice husk to nanocrystalline silica - Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Journal of American Chemical Society, 2006)
Rice husk is a cheap agro-based waste material, which harbors a substantial amount of silica in the form of amorphous hydrated silica grains. However, there have been no attempts at harnessing the enormous amount of amorphous silica present in rice husk and its room-temperature biotransformation into crystalline silica nanoparticles. In this study, we address this issue and describe how naturally deposited amorphous biosilica in rice husk can be bioleached and simultaneously biotransformed into high value crystalline silica nanoparticles. We show here that the fungus Fusarium oxysporum rapidly biotransforms the naturally occurring amorphous plant biosilica into crystalline silica and leach out silica extracellularly at room temperature in the form of 2-6 nm quasi-spherical, highly crystalline silica nanoparticles capped by stabilizing proteins; that the nanoparticles are released into solution is an advantage of this process with significant application and commercial potential. Calcination of the silica nanoparticles leads to loss of occluded protein and to an apparently porous structure often of cubic morphology. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential cheap agro-industrial waste materials is an exciting possibility and could lead to an energy-conserving and economically viable green approach toward the large-scale synthesis of oxide nanomaterials.

Fungus-based synthesis of chemically difficult-to-synthesize multifunctional nanoparticles of CuAlO2 - Ahmad, Absar; Jagadale, Tushar C.; Dhas, Vivek V.; Khan, Shadab; Patil, Shankar; Pasricha, Renu; Ravi, Venkat; Ogale, Satishchandra B. (Advanced Materials, 2007)
Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 degrees C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein-capped water-dispersible nanoparticles show blue luminescence and radio-frequency absorption (see figure).

Fungus mediated synthesis of biomedically important cerium oxide nanoparticles - Khan, Shadab Ali; Ahmad, Absar (Materials Research Bulletin, 2013)
Nanomaterials can be synthesized by chemical, physical and the more recently discovered biological routes. The biological routes are advantageous over the chemical and physical ones as unlike these, the biological synthesis protocols occur at ambient conditions, are cheap, non-toxic and eco-friendly. Although purely biological and bioinspired methods for the synthesis of nanomaterials are environmentally benign and energy conserving processes, their true potential has not been explored yet and attempts are being made to extend the formation of technologically important nanoparticles using microorganisms like fungi. Though there have been reports on the biosynthesis of oxide nanoparticles by our group in the past, no attempts have been made to employ fungi for the synthesis of nanoparticles of rare earth metals or lanthanides. Here we report for the first time, the bin-inspired synthesis of biomedically important cerium oxide (CeO2) nanoparticles using the thermophilic fungus Humicola sp. The fungus Humicola sp. when exposed to aqueous solutions of oxide precursor cerium (III) nitrate hexahydrate (CeN3O9 center dot 6H(2)O) results in the extracellular formation of CeO2 nanoparticles containing Ce (III) and Ce (IV) mixed oxidation states, confirmed by X-ray Photoemission Spectroscopy (XPS). The formed nanoparticles are naturally capped by proteins secreted by the fungus and thus do not agglomerate, are highly stable, water dispersible and are highly fluorescent as well. The biosynthesized nanoparticles were characterized by UV-vis spectroscopy, Photoluminescence spectroscopy (PL), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and X-ray Photoemission Spectroscopy (XPS). (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electron microscopy; Nanostuctures; Optical properties; Oxides; X-ray diffraction

Fungus-mediated preferential bioleaching of waste material such as fly - ash as a means of producing extracellular, protein capped, fluorescent and water soluble silica nanoparticles - Khan, Shadab Ali; Uddin, Imran; Moeez, Sana; Ahmad, Absar (PLoS One, 2014)
In this paper, we for the first time show the ability of the mesophilic fungus Fusarium oxysporum in the bioleaching of waste material such as Fly-ash for the extracellular production of highly crystalline and highly stable, protein capped, fluorescent and water soluble silica nanoparticles at ambient conditions. When the fungus Fusarium oxysporum is exposed to Fly-ash, it is capable of selectively leaching out silica nanoparticles of quasi-spherical morphology within 24 h of reaction. These silica nanoparticles have been completely characterized by UV-vis spectroscopy, Photoluminescence (PL), Transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Energy dispersive analysis of Xrays (EDAX).